Aflatoxin Contamination of Mustard and Taramira Seeds Under Storage in Rajasthan - Podder, Shipra Rani; Purohit, D K (Annals of Arid Zone, 2016)
Aspergillus flavus strains isolated from seeds of mustard (Brasscia juncea) and taramira (Eruca sativa) collected from different parts of Rajasthan were screened for aflatoxin producing potentials. Forty nine out of 50 and 71 out of 75 isolates from mustard and taramira respectively were toxigenic and elaborated varying amount of aflatoxins. Similarly when 27 and 38 naturally infested samples of taramira and mustard were analysed for the presence of aflatoxins. 13 and 10 samples were positive for aflatoxin contamination. Aflatoxin B1 was invariably present in all the contaminated samples and the amount of aflatoxin B varied from trace to 489 ug/kg in taramira.while in mustard it ranged from trace to 729ug kg-1.